(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Some of the major issues that these cyber infrastructures must deal with include issues like privacy, trust, and security. With these smart gadgets, an automated environment may be created in fields such as military, manufacturing, e-healthcare, and so on. These technologies helped to create the Medical Cyber Physical System in e-healthcare (MCPS). CPS are varied and can incorporate a wide range of technologies. However, the security issues found in the upper levels of this taxonomy are more closely linked to those found in other KAs that deal with more traditional security issues. Because of this, the emphasis of this paper is on elements of CPS that are more directly linked to the detection, control and actuation of these systems.